Are we all Bédierian? Perspectives for Digital Genetic Editions - Beatrice Nava (Umanistica Digitale, 2023)
The current scene of Digital Scholarly Editions, particularly those concerning modern manuscripts, registers a trend towards documentary and diplomatic editions. This “bédierian” tendence leads to editions focused mainly on the diplomatic transcription of the source, lacking in consideration about the genetic process. Lying under this situation we could figure out the existence of digital tools and languages more adequate to this documentary approach. In addition to that, this article is aimed at showing the concrete problems in representing the diachronic elaboration of the text in a digital form, through methodological considerations and examples of realisation. Despite the widespread trend and the difficulty in choosing a different way, it seems possible to reflect on genetic digital editions from an optimistic perspective. In fact, these editions are not only necessary, at least for certain textual situations, but also feasible, as shown by some ongoing projects and experiments (Saba 2021, VaSto 2022 and Il Conte di Carmagnola), presented at the end of the contribution.